PENGARUH KOMPETENSI, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi Kasus Pada CV San Juan Semarang) (Students' Journal of Economic and Management, 2015)
This study analyzed the effect of competence, work discipline, and motivation on employee performance. Object of study in this paper is the CV San Juan Semarang. The sampling technique in this research is to use simple random sampling (random) sample of 60 respondents as a data collection method using a questionnaire (questionnaire) by distributing a list of questions to the respondent in order to obtain information. The research objective was formulated to determine the effect of competence, work discipline and motivation on employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of each of the independent variables were tested by regression analysis. The results of the research are: (1) Competence has a positive and significant influence on employee performance. (2) Work Discipline has a positive and significant impact on employee performance. (3) Motivation has a positive and significant impact on employee performance. Keywords: Competence , Work Discipline and Motivation